Difficulties and coping strategies of student in learning mathematics according to their proficiency level - Cabanalan, Jun Felip A (Iloilo City University of the Philippines Visayas, 2018)
This study aimed to know the difficulties and coping strategies of students in learning mathematics, specifically, as a whole and according to their proficiency level. It was conducted to 24 Grade 10 students of Gines National High School S.Y. 2015-2016. Participants were selected using convenience sampling from proficient, approaching proficiency and developing groups. The researcher-made questionnaire was the instrument used to gather data and in-depth interview followed to confirm their responses and to get other information. Examination results were examined and the Devised Coping Strategy Inventory Tool was administered to validate difficulties and coping techniques of students. Obtained data were analyzed using frequency and percentage for mathematics difficulties, and Thematic Data Analysis, mean and standard deviation for coping strategies. Results of this study showed that regardless of proficiency level, students find arithmetic, information, language, and visual spatial difficult. Taking down notes, spending time for review, sitting near front, and listening attentively were primarily the coping styles of students in mathematics. Students of developing, approaching proficiency and proficient groups differed with the use of sitting-aea media (concluded that student experiencing these difficulties in mathematics lack skills and cognitive abilities. Students face the same difficulties but at different individually. The students who listened more attentively, often seated near front of the class and frequently asked teacher questions were the proficient students.
Special Problem (M. Ed. - Mathematics) -- Iloilo City : University of the Philippines Visayas, September 2018.